A new Co(II)-bearing coordination polymer: structural characterization and treatment effect on CVB3-induced myocarditis via suppressing inflammatory response. Issue 4 (2nd April 2020) - Yu, Li-Jun; Bai, Dong-Song; Tang, Wen-Li; Bi, Fu-Long; Zhao, Ming; Li, Zhi-Hu
Abstract: By employment of the mixed-ligand approach, a new Co(II)-based coordination polymer with the chemical formula of [Co(ox)(ditb)] (1, ox = oxalic acid, ditb = 1, 4-di(1H-1, 2, 4-triazol-1-yl)butane) was successfully obtained. Furthermore, a green hand grinding technique has been implemented to reduce the particle size of the complex 1 to generate nanoscale 1 (denoted as nano 1 hereafter) with sheet-like morphology. To evaluate the protective of the nano 1, the histopathology evaluation of the CVB3-induced myocarditis animal model was performed. To reveal the relationship between the cell inflammatory response and the compound protective effect, the ELISA was conducted to determine the content of IL-1 and TNF-α in the myocardial tissue.